Determining Amino Acid Digestibility of Soybean Meal from South Carolina Soybean Varieties Fed to Broilers - Kara M. Dunmire; Michaela B. Braun; Caitlin E. Evans; Benjamin D. Fallen; Charles R. Stark; Chad B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2021)
At hatch, 240 male broilers (Ross 308, Aviagen, Sallisaw, OK) were placed in batteries (Petersime Brood Unit, Gettysburg, OH) for a 15-d study to evaluate amino acid digestibility of soybean meal (SBM) from specialty variety soybeans grown in South Carolina. There were 10 replicates per treatment and 6 broilers per cage. Broilers were given a common corn and soybean meal-based diet from d 0 to 9. On d 9, broilers were weighed, and cages were allotted to 1 of 4 dietary treatments within location block. Dietary treatments consisted of 1 of 4 soybean sources varying in quality determined by crude protein (CP) content and processed into SBM. Two sources consisted of soybeans from a similar region and processed either commercially solvent extracted or experimentally solvent extracted at Texas A&M University. Therefore, dietary treatments consisted of a commercially processed SBM with 44% CP (CON) or experimentally processed SBM with 50% CP (PCON), 52% CP (52SBM), or 56% CP (56SBM). Assay diets were dextrose and SBM-based, formulated to supply 20% dietary CP with titanium dioxide as an indigestible marker. On d 15, broilers were euthanized by CO2inhalation and ileal samples were collected for determination of apparent ileal digestibility (AID) of AA. Data were analyzed using the GLIMMIX procedure in SAS v. 9.4 (SAS Institute Inc., Cary, NC), with pen as the experimental unit, pen location as the blocking factor and adjusted using Tukey-Kramer multiple comparisons. Broilers fed CON and 56SBM had increased (P<0.003) digestibility of total AA, Arg, His, Lys, Thr, and Trp compared to those fed PCON and 52SBM. Digestibility of Ile and Phe increased (P<0.001) in broilers fed 56SBM compared to CON and 52SBM, while PCON was intermediate to CON and 52SBM. Broilers fed 56SBM had increased (P<0.001) digestibility of Leu compared to all other sources. Digestibility of Met increased (P = 0.007) in broilers fed CON and 56SBM compared to 52SBM and there was no evidence for differences between those fed PCON and all other sources. Broilers fed CON and 56SBM had increased (P<0.001) digestibility of Val compared to PCON and 52SBM, with no evidence for differences between those fed CON and PCON. In conclusion, broilers fed commercially processed SBM had improved AA digestibility compared to those fed experimentally processed soybeans from a similar region. The high CP (57% CP) SBM variety had increased AA digestibility compared to the PCON and 52SBM.
Keywords: poultry; amino acid digestibility; broilers; soybean meal; soybean variety